Intestinal transit in anxiety and depression. - Gorard, D A (1996)
BACKGROUND: Patients with anxiety and depression often have bowel symptoms. Until now, studies investigating a link between altered bowel habit and psychological illness have focused on patients with disturbed defecation presenting to gastroenterologists. AIMS: To determine whether patients with anxiety and depression have objective evidence of abnormal intestinal transit irrespective of any bowel symptoms. METHODS: 21 psychiatric outpatients fulfilling research criteria for generalised anxiety disorder and/or major depression, and 21 healthy volunteers were studied. Orocaecal transit time (OCTT) was measured by lactulose hydrogen breath test. Whole gut transit time (WGTT) was measured by abdominal radiography after ingestion of radio-opaque markers. RESULTS: Median (range) WGTT was shorter in patients with anxiety (14 (6-29) hours) than in patients with depression (49 (35-71) hours) (p < 0.001), and controls (42 (10-68) hours) (p < 0.001). In patients with anxiety, orocaecal transit time was shorter (60 (10-70) minutes) than in patients with depression (110 (60-180) minutes) (p < 0.01), and shorter than in controls (75 (50-140)) minutes (p < 0.05). The prolongation of transit times in depression compared with controls was not significant. However, WGTT correlated with both the Beck Depression Inventory score (r = 0.59, p < 0.01) and the depression score of the Hospital Anxiety and Depression scale (r = 0.66, p < 0.001). CONCLUSIONS: These objective measurements of intestinal transit in affective disorders are consistent with clinical impressions that anxiety is associated with increased bowel frequency, and depressed patients tend to be constipated; mood has an effect on intestinal motor function.